Development of QCT loaded TPGS coated solid lipid nanoparticles for improved in vivo neuroprotective activity in LPS administered adult zebrafish model: A QbD-based approach - Galal Mohsen Hussein Al-sayadi; Gurisha Garg; Arti Singh; Preeti Patel; Ghanshyam Das Gupta; Balak Das Kurmi (Elsevier, 2024)
This work contains the development of QCT-loaded TPGS-coated SLNs by QbD to enhance neuroinflammation potential. Developed SLNs were in the nanometer range (263±3.62 nm) with desired parameters i.e., PDI (0.244±0.003), zeta potential (28.2 ± 0.74 mV), and%EE (74.3 ± 2.45 %) respectively. The release study showed sustained drug release of the developed formulation T-QCT-SLN (83.2 % release in 48 h). The study found QCT can reduce oxidative stress and neuroinflammation in adult zebrafish. Results showed reduced disruption in neuronal cells, decreased TNF-α and IL-1β levels, and reduced LPO, nitrite, and AChEs levels while increasing GSH levels, indicating its potential for treating oxidative stress and neuroinflammation. It can be concluded that QCT-loaded TPGS-coated SLN effectively prevents oxidative damage and neuroinflammation in adult zebrafish exposed to LPS compared to the QCT alone. The suggested work will be a focal paradigm for neuroinflammatory drug delivery.